Study for pediatric protocol optimization in chest CT scans (Brazilian Journal of Radiation Sciences, 2019)
Radiological exams are increasingly used in clinic for diagnostic analysis of different types of pathologies. These tests are associated with a dose that is received by the patient. In addition, the risks in exposure to ionizing radiation are different according to the group which the individual belongs. According to age, the group of children is more radiosensitive than adults. In this work we have obtained values of the air-weighted kerma index for chest scans studies in a Genereal Electric Computed Tomography (CT) scanner model Discovery with 64-channels. Using an adult protocol, two scans have been performed, one using a cylinder standard PMMA phantom while the second one has used an oblong chest phantom designed for a two year old pediatric patient. Furthermore, other protocols have been selected by varying the X-ray tube current but maintaining the same voltage, in order to obtain a reduction in the dose received by the pediatric patient but maintaining the image quality. The use of the adult protocol in the child phantom has generated a value in the air-weighted kerma index 89.47% greater than that received using the adult phantom. As small patients receive higher doses, the use of specific protocols for children is important for the dose reduction in CT tests. Due to the different characteristics of CT scanners and in order to optimize these protocols with regard to dose and diagnostic image quality, there is a need to have pediatric phantoms in health centers